Mini-ID – A minimally invasive drainage strategy for complicated skin and soft tissue infection - Patrick Szu-Ying Yen; Chao-Wei Chang; Hou-Yuen Tong; Yun-Nan Lin (Medicine, 2026)
Rationale: Complicated skin and soft tissue infections (cSSTIs) are severe infections that may arise from abscesses, cellulitis, fasciitis, diabetic foot infections, trauma-related infections, and surgical site infections. Conventional treatment typically requires surgical drainage combined with systemic antibiotics. However, exploratory surgical drainage may cause tissue damage and increase inflammatory responses. Patient concerns: A 35-year-old male with diabetic ketoacidosis presented with progressive swelling, erythema, and pain in the right upper arm despite prior antibiotic therapy. Diagnosis: Complicated skin and soft tissue infection with localized abscess formation. Interventions: After the patient was stabilized and was treated using a minimally invasive sequential management strategy termed Mini-ID, which consists of minimal drainage, infection control, inflammation control, and adequate debridement. Drainage was performed using a skin biopsy punch instrument to minimize tissue damage. Culture-guided antibiotic therapy was subsequently administered. Outcomes: The patient demonstrated rapid clinical improvement with a significant reduction in inflammatory markers and complete wound healing at 3 months without requiring extensive surgical intervention. Lessons: The Mini-ID approach emphasizes that adequate source control rather than the extent of surgical incision may be sufficient in selected cSSTI cases. This strategy may reduce tissue injury and inflammatory burden while maintaining clinical effectiveness.